Heregulin ameliorates the dystrophic phenotype in mdx mice. - Krag, T; Bogdanovich, S; Jensen, C; Fischer, M; Hansen-Schwartz, J; Javazon, E; Flake, A; Edvinsson, L; Khurana, T (2004)
Duchenne's muscular dystrophy (DMD) is a fatal neuromuscular disease caused by absence of dystrophin. Utrophin is a chromosome 6-encoded dystrophin-related protein (DRP), sharing functional motifs with dystrophin. Utrophin's ability to compensate for dystrophin during development and when transgenically overexpressed has provided an important impetus for identifying activators of utrophin expression. The utrophin promoter A is transcriptionally regulated in part by heregulin-mediated, extracellular signal-related kinase-dependent activation of the GABP(alpha/beta) transcription factor complex. Therefore, this pathway offers a potential mechanism to modulate utrophin expression in muscle. We tested the ability of heregulin to improve the dystrophic phenotype in the mdx mouse model of DMD. Intraperitoneal injections of a small peptide encoding the epidermal growth factor-like region of heregulin ectodomain for 3 months in vivo resulted in up-regulation of utrophin, a marked improvement in the mechanical properties of muscle as evidenced by resistance to eccentric contraction mediated damage, and a reduction of muscle pathology. The amelioration of dystrophic phenotype by heregulin-mediated utrophin up-regulation offers a pharmacological therapeutic modality and obviates many of the toxicity and delivery issues associated with viral vector-based gene therapy for DMD.